2008
DOI: 10.1152/ajplung.90215.2008
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke-induced expression of heme oxygenase-1 in human lung fibroblasts is regulated by intracellular glutathione

Abstract: Baglole CJ, Sime PJ, Phipps RP. Cigarette smoke-induced expression of heme oxygenase-1 in human lung fibroblasts is regulated by intracellular glutathione. Am J Physiol Lung Cell Mol Physiol 295: L624 -L636, 2008. First published August 8, 2008 doi:10.1152/ajplung.90215.2008.-Fibroblasts are key structural cells that can be damaged by cigarette smoke. Cigarette smoke contains many components capable of eliciting oxidative stress, which may induce heme oxygenase (HO)-1, a cytoprotective enzyme. There are no d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
86
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 75 publications
3
86
1
Order By: Relevance
“…We have previously shown that CDDO potently up-regulates expression of oxidative stressresponse proteins in a glutathionedependent manner and that NAC inhibits this up-regulation (29,41). Here, we show that NAC blocks up-regulation of HO-1 but does not inhibit the ability of CDDO to reduce TG2 expression ( Figure 5C).…”
Section: Discussionsupporting
confidence: 55%
“…We have previously shown that CDDO potently up-regulates expression of oxidative stressresponse proteins in a glutathionedependent manner and that NAC inhibits this up-regulation (29,41). Here, we show that NAC blocks up-regulation of HO-1 but does not inhibit the ability of CDDO to reduce TG2 expression ( Figure 5C).…”
Section: Discussionsupporting
confidence: 55%
“…HPAEC led to an increase in LT formation in response to A23187 (39). In the current study, we observed that t-HBEC cells also show relatively low levels of 5-LO mRNA, which did not change in response to hypoxia (data not shown), Thus t-HBEC were transfected with a 5-LO expression plasmid.…”
Section: Hypoxia-mediated Lt Formation In Endothelial Cells Requires mentioning
confidence: 46%
“…Chiba et al (43) have reported that AhR activation in airway epithelial cells induces mucin secretion through production of ROS, suggesting that antioxidant treatments may be appropriate for patients with respiratory symptoms related to dioxin exposure. On the contrary, Baglole et al (44) have shown that AhR activation by cigarette smoke extracts has a protective effect on airway inflammation by inducing the production of the cytoprotective enzyme heme-oxygenase-1 by lung fibroblasts. The discrepancy between these results may be ascribed to the model (human versus mouse cell lines), the mechanism (structural damage versus inflammation), and AhR agonists adopted.…”
Section: Discussionmentioning
confidence: 96%